SAT0645-HPR Results of A Goal Management Intervention for Patients with Polyarthritis with Mild Depressive Symptoms. (15th July 2016) - Arends, R.; Bode, C.; Taal, E.; van de Laar, M.
Abstract : Background: Persisting disease symptoms can threaten attainment of personal important goals for patients with polyarthritis, resulting in elevated levels of depression and anxiety 1 . Interventions that provide patients with the skills and techniques to live with and manage their disease in daily life are essential, as people have to manage a chronic disease most of the time outside of the health-care system. For this purpose participants practice four goal management competencies (goal maintenance, goal adjustment, goal disengagement and goal re-engagement) and the flexible use of these strategies during the self-management intervention "Right on Target". Objectives: The purpose of this study was to establish whether an intervention aimed at increasing goal management capacities is effective in decreasing symptoms of depression and increasing adaptation in patients with polyarthritis with elevated levels of depressive symptoms. Methods: In total, 85 persons with a diagnosis of polyarthritis and elevated levels of depression received the group-based goal management intervention Right on Target with measurements at baseline, post-intervention (after 2 months) and follow-up (6 months). A quasi-experimental design was applied in which the reference group consisted of 151 participants of a previously conducted observational study selected according to the inclusion criteria for the intervention group. Primary outcome was depression, secondary outcomes anxiety, purpose in life, positive affect and satisfaction with participation. Mediating variables were goal management strategies and arthritis self-efficacy. Linear mixed model procedure was applied to evaluate changes in outcomes. Proportions showing clinically relevant changes and possible mediators were analyzed. Results: No improvement was found for depressive symptoms. Positive affect significantly improved in the intervention group mediated by an increase in goal adjustment. No changes were found for the other secondary outcomes, while goal maintenance decreased and self-efficacy for other symptoms than pain increased in the intervention group. Conclusions: This study indicates the value of improving the management of personal threatened goals of people with polyarthritis and showed that especially facilitating goal adjustment and downgrading goal tenacity are potentially helpful. While more research is needed, the present study provides a small but promising direction towards greater wellbeing for patients with polyarthritis. References: Arends RY, Bode C, Taal, E & van de Laar MAFJ. The longitudinal relation between patterns of goal management and psychological health in people with arthritis: The need for adaptive flexibility. BJHP, 2016, DOI:10.1111/bjhp.12182 Disclosure of Interest: None declared